2016
DOI: 10.1042/bcj20160200
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Cx26 variants established functional heterotypic Cx26/Cx43 and Cx26/Cx40 gap junction channels

Abstract: Gap junction (GJ) channels mediate direct intercellular communication and are composed of two docked hemichannels (connexin oligomers). It is well documented that the docking and formation of GJs are possible only between compatible hemichannels (or connexins). The mechanisms of heterotypic docking compatibility are not fully clear. We aligned the protein sequences of docking-compatible and -incompatible connexins with that of connexin26 (Cx26). We found that two docking hydrogen bond (HB)-forming residues on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…CX26 association with other CX has also been disclosed by global interactome analyses [ 33 ]. CX26 physical interaction with paralogues is, therefore, a common feature since it is for other family members [ 43 ]. Few additional binding partners have been reported for CX26.…”
Section: Discussionmentioning
confidence: 99%
“…CX26 association with other CX has also been disclosed by global interactome analyses [ 33 ]. CX26 physical interaction with paralogues is, therefore, a common feature since it is for other family members [ 43 ]. Few additional binding partners have been reported for CX26.…”
Section: Discussionmentioning
confidence: 99%
“…For hCx46, the N188 formed corresponding hydrogen bonds with R180, T189, and D191. The importance of N176 and K168 for the docking interaction was recently demonstrated by Karademir et al (2016) [ 21 ]. The authors showed that by adapting the homologous residues, heterotypic docking between Cx26 and Cx40 connexons could be achieved.…”
Section: Introductionmentioning
confidence: 97%
“…The gap junction channels formed by different connexins are functionally distinct with respect to their gating, conductance, and permeability characteristics. The complexity of these channels is emphasized by the fact that hemichannels and complete gap junction channels can be either homotypic or heterotypic (Karademir, Aoyama, Yue, Chen, & Bai, ; Koval, Molina, & Burt, ). Consequently, genetic mutations in a single connexin gene may impact formation of many types of channels, thus contributing to the phenotypic spectrum of diseases that result from such mutations.…”
Section: Introductionmentioning
confidence: 99%